牙嵌式离合器速差特性研究 - 郭占正; 张吉吉玉; 张建峰; 苑士华 (Jixie chuandong)
The basic principles of jaw clutch is introduced.The classification of engaging situation and detailed analysis of engaging process of each is built based on the relative position of engaging parts.The smooth engaging successfully of a variety of situations is identified.The smooth joint to the allowed speed differences is analyzed in detail.The mainly affect parameter and the law is determined.